Analisis Potensi Stok Karbon dan Strategi Peningkatan Kualitas Ruang Terbuka Hijau di Kecamatan Tenggilis Mejoyo, Surabaya - Criselli Naftalia, Hana; Aussie Amalia (Jurnal Serambi Engineering, 2025)
Tenggilis Mejoyo Sub-district, Surabaya, has significant potential for Green Open Spaces (GOS) to support carbon emission reduction in urban areas. This study aims to analyse the carbon stock potential of GOS in the area and evaluate their role in carbon emission mitigation. Primary data were collected through field surveys measuring tree diameter and height using the allometric method, while secondary data were obtained from relevant literature. The results show that the total area of green lanes in Tenggilis Mejoyo is 33,227.5 m², with a carbon storage capacity of 275.35 tonnes. This capacity can only absorb 0.33% of the total carbon dioxide (CO₂) emissions from the transport sector in 2019, which amounted to 83,336.73 tonnes, leaving 83,061.38 tonnes/year unabsorbed. An additional 145.97 hectares of GOS are required to offset the remaining carbon emissions. This study also shows that active parks were not included in the carbon stock analysis, which are likely to increase the overall contribution to carbon sequestration. Therefore, further research on carbon stocks in active parks within Tenggilis Mejoyo is highly recommended. The results of this study are expected to serve as a basis for environmental policy planning and more effective GOS management in Surabaya.